ChemInform Abstract: Keggin‐Type Broensted Dodecatungstophosphoric Acid: A Quasi Homogenous and Reusable Catalyst System for Liquid Phase Beckmann Rearrangement. Issue 28 (15th July 2014) - Kaur, Gagandeep; Rajput, Jaspreet Kaur; Arora, Priya; Devi, Nisha
Abstract An efficient, clean, eco‐friendly, and simple method for the title reaction by employing H3PW12O40 as catalyst is developed.